Experimental Parametric Analysis of Biodiesel Synthesis in Microreactors with Waste Cooking Oil - Paiz, Saxon (2020)
Submitted by Daniele Fonseca (daniele@ct.ufrj.br) on 2020-04-29T14:44:03Z No. of bitstreams: 1 SaxonPaiz.pdf: 8812145 bytes, checksum: 5b96b87b3df2e564a753e81590ec217c (MD5)